Exploring the Factors That Influence Consumer’s Purchase of Mobile Phones - Mohd Yusuf, Bibi Noraini; Hock, Lim Lye; Abd Rashid, Intan Maizura; Saaban, Syahira; Sham Abdullah, Muhammad Fazlee (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
Nowadays smart phone has become a new social need and trend especially among the younger age groups, thus generating rapid and vast demand for all mobile phone brands. Interestingly, dealers of smart phones need to understand what factors affect such demand, typical features as well as characteristics of the buyers. The main objective of this study is to understand how price, social influences, relative advantage and brand image affect demand of smart phones in the northern regions of Malaysia, where the State of Perlis has been chosen. The primary data of this study was collected by distributing randomly 120 sets of questionnaires to respondents who live in Perlis. The responses obtained were analyzed by several statistical tools namely frequency distribution, mean, standard deviation analysis, Cronbach’s Alpha Reliability test, Person Correlation Coefficient and Linear Regression Analysis, computed by a data software, Package for the Social Science (SPSS) version 17.0. This study revealed that price, social influences, relative advantage and brand image have significant relationships towards demand of smart phones. Detailed discussion of the study objectives, literature review, theories, research limitations, conclusions and finally some recommendations for future research study are given below. It is our hope that the results of the study can help mobile phone companies to have better understanding of the features of the smart phone market, be able to produce quality products and improve their marketing strategies.